Systematic Literature Review of Real-World Evidence on Dose Escalation and Treatment Switching in Ulcerative Colitis - Singh H; Wilson L; Tencer T; Kumar J (Dove Medical Press, 2023)
Harpreet Singh,1 Liam Wilson,2 Tom Tencer,3 Jinender Kumar3 1Health Economics & Market Access (HEMA), Amaris Consulting Ltd, Toronto, ON, Canada; 2Health Economics & Market Access (HEMA), Amaris Consulting Ltd, Shanghai, People's Republic of China; 3Bristol Myers Squibb, Princeton, NJ, USACorrespondence: Jinender Kumar, Global HEOR, Bristol Myers Squibb, 100 Nassau Park Blvd #300, Princeton, NJ, 08540, USA, Tel +1-609-302-7630, Email Jinender.Kumar@bms.comBackground: Currently approved biologic therapies for moderate-to-severe ulcerative colitis have well-established efficacy. However, many patients fail to respond or lose response, leading to dose escalation or treatment switching.Objective: We sought to identify real-world evidence on dose escalation and treatment switching and associated clinical and economic outcomes among adults with ulcerative colitis treated with infliximab, adalimumab, golimumab, vedolizumab, ustekinumab, or tofacitinib.Methods: We conducted a systematic search of Embase, MEDLINE (up to 26 August 2020), and conference proceedings (2017− 2020) for studies in adults with ulcerative colitis to assess clinical response and remission, colectomy, adverse events, and economic outcomes related to dose escalation and treatment switching.Results: In 56 studies, dose escalation and treatment switching involving infliximab and/or adalimumab were most frequently investigated. Rates of clinical response after dose escalation were 20- 95% (1.8- 36 months), clinical remission rates were 10- 94% (1.8- 36 months), colectomy rates were 0- 33% (12- 38 months), and adverse event rates were 0- 18%. Treatment switching rates in 21 studies were 4- 70% over 3- 62 months, with switch due to loss of response rates of 4- 35% over 12- 62 months (7 studies). Up to 35% of patients underwent colectomy 12− 120 weeks after switching, and 13- 38% experienced adverse events. Data relating to economic outcomes were limited to tumor necrosis factor inhibitors, but demonstrated increased direct costs associated with both dose escalation and treatment switching.Conclusion: Dose escalation and treatment switching are common with existing therapies. However, clinical response and remission rates vary, and a proportion of patients fail to achieve optimal clinical and economic outcomes. This highlights the need for more efficacious and durable treatments for patients with moderate-to-severe ulcerative colitis.Keywords: ulcerative colitis, real-world evidence, systematic literature review, biologic therapies, tofacitinib